Pengaruh Penerapan Strategi Pelaksanaan Perilaku Kekerasan terhadap Tanda Gejala Klien Skizofrenia di Rumah Sakit Jiwa Daerah Provinsi Jambi - Siti Makhruzah; Vevi Suryenti Putri; Rahmi Dwi Yanti (Jurnal Akademika Baiturrahim Jambi, 2021)
The prevalence of violent behavior committed by people with schizophrenia is 19.1%. One of the nurse's independent actions is the provision of implementation Strategy on the client's violent behavior. The study aimed to determine the influence of applying the strategy of implementing violence behavior toward signs symptoms of schizofrenia clients at psychiatric hospital Jambi province. This study was conducted from 01st to 22nd January 2020. It used preexperimental with one group pre and post test design. The populations were all of schizophrenic clients with violent behavior who were hospitalized with sample as many as 30 people. The collecting of data was conducted by using purposive sampling technique. The findings were obtained that mean value of signs symptom pre-test 17.0 and after the implementing of SP is determined to occur a decrease in the mean value of post-test symptoms of 7.93. Bivariate analysis with the t test obtained p value of 0,000 (<0.05) so that there is an influence of the implementation of the PK implementation strategy on the decrease in symptoms